P3.101 Effectiveness of prenatal screening to prevent congenital syphilis, florida and louisiana, 2013–2014. (8th July 2017) - Matthias, James; Rahman, Mohammad; Newman, Daniel; Peterman, Tom
Abstract : Introduction: Between 2012 and 2014, rates of congenital syphilis increased in Louisiana (LA) (from 52.7 to 73.4 cases per 1 00 000 live births) and Florida (FL) (from 17.4 to 22.1 cases per 1 00 000 live births) ranking them among the highest in the United States. Both states have rules and regulations that require testing pregnant women for syphilis during the first trimester, early third trimester, and at delivery. We evaluated the effectiveness of early and third trimester syphilis screening for the prevention of congenital syphilis in these high-morbidity states. Methods: Reported syphilis cases among pregnant women in FL and LA during January 1, 2013–December 31, 2014, were reviewed for documented screening for syphilis in the first two trimesters and the third trimester. Pregnant women with syphilis were linked to congenital syphilis records and stratified by whether their pregnancy led to a reported congenital syphilis case. Results: 710 pregnant women with syphilis in LA and FL led to 155 congenital syphilis cases. 555 (78%) potential congenital syphilis cases were averted. 370 (52%) of the pregnant women with syphilis were staged as early syphilis or high-titer late-latent syphilis, and they were linked to 109 (70%) of the congenital syphilis cases. 513 pregnant women tested positive for syphilis in the first two trimesters and 470 (92%) of them had babies without congenital syphilis. Of the remaining 197 women, 109 tested positive for syphilis in the third trimester, and 85 (78%) of them had babies without congenital syphilis. 39 (6%) women had no reported syphilis screening ≥30 days prior to delivery. 85 women had at least one negative screening test during pregnancy before the positive test, and 55 of them had a baby with congenital syphilis. Conclusion: Screening for syphilis both early and in the third trimester prevented many pregnant women with syphilis from having a baby with congenital syphilis. Preventing all congenital syphilis would likely require preventing all syphilis among women.